Evaluation of a simple disposable microband electrode device for amperometric gas sensing - Xiong, L; Goodrich, P; Hardacre, C; Compton, R (2013)
We report a simple and facile methodology for constructing Pt (6.3 mm × 50 μm) and Cu (6.3 mm × 30 μm) annular microband electrodes for use in room temperature ionic liquids (RTILs) and propose their use for amperometric gas sensing. The suitability of microband electrodes for use in electrochemical analysis was examined in experiments on two systems. The first system studied to validate the electrochemical responses of the annular microband electrode was decamethylferrocene (DmFc), as a stable internal reference probe commonly used in ionic liquids, in [Pmim][NTf2], where the diffusion coefficients of DmFc and DmFc+ and the standard electron rate constant for the DmFc/DmFc+ couple were determined through fitting chronoamperometric and cyclic voltammetric responses with relevant simulations. These values are independently compared with those collected from a commercially available Pt microdisc electrode with excellent agreement. The second system focuses on O2 reduction in [Pmim][NTf2], which is used as a model for gas sensing. The diffusion coefficients of O2 and O2-̇ and the electron transfer rate constant were again obtained using chronoamperometry and cyclic voltammetry, along with simulations. Results determined from the microbands are again consistent to those evaluated from the Pt microdisc electrode when compared these results from home-made microband and commercially available microdisc electrodes. These observations indicate that the fabricated annular microband electrodes are suitable for quantitative measurements. Further the successful use of the Cu electrodes in the O2 system suggests a cheap disposable sensor for gas detection. © 2013 Elsevier B.V.